An Introduction to Text Mining - Wallace, Niamh; Feeney, Mary (Qualitative and Quantitative Methods in Libraries; Vol 7 No 1 (2018): March 2018 Issue, 2019)
Scholars in the digital humanities and other disciplines utilize a variety of qualitative and quantitative methods in their research. One of these methodologies – textual analysis – can be facilitated by the use of text mining digital tools, such as Voyant, ATLAS.ti, JSTOR Data for Research, and Google's Ngram Viewer. Supporting digital scholarship is an important and expanding role for academic libraries, from providing resources for text mining to collaborating with digital scholars. This paper gives a brief overview of text mining, explores some of the available tools, and discusses limitations and challenges. It also shares examples of text mining projects and examines how libraries can offer expertise and services to support this research, including the provision of corpora for text analysis and the integration of digital tools in courses.